Evaluation on clinical efficacy of Fuzheng Jiedu Huayu Decoction combined with antibiotics in the treatment of pneumonia in the elderly – A multi-center, double-blind, parallel, randomized controlled trial. (April 2018) - Xu, Hongri; Li, Meng; Wang, Chengxiang; Yin, Renyi; Ma, Jie; Wang, Mingzhe; Tan, Quan Ming; Jiang, Liangduo; Cheng, Miao; Chen, Xianhai; Zhang, Lishan; Su, Huiping; et al.
Abstract: Objective: To evaluate the efficacy and safety of Fuzheng Jiedu Huayu Decoction (FJHD) in treating pneumonia in the elderly. Methods: Adopting a multi-center, double-blind, parallel, randomized controlled trial, 284 elderly pneumonia patients were enrolled and randomly allocated to the standard treatment with FJHD (treatment group, TG) and the standard treatment with placebo group (control group, CG). Efficacy and safety was evaluated through mortality rate, curative rate, symptom improvement, chest X-ray (CXR) lesion absorption, arterial blood gas (ABG), peripheral blood leukocyte count (PBLC) and adverse events. Results: There was no significant difference in mortality rate between both groups ( P > 0.05). TG significantly enhanced the curative rate of a 2-week treatment course ( P < 0.05). Compared with CG, TG significantly decreased the expectoration score during the first and second week of treatment ( P < 0.05). During the first week, improvement in expectoration was conducive to airway patency. During the second week, wheezing, shortness of breath and other symptoms were also significantly improved. During the third week, body temperature was stable. TG improved lesion absorption with Pneumonia Severity Index (PSI) class II ( P < 0.05) and SMART-COP score 1 ( P < 0.05). TG significantly decreased the arterial carbon dioxide partial pressure after a 1-week treatment. There were no serious adverse events in TG. Conclusion: Standard anti-infection treatment with FJHD is a safe and reliable method of treating elderly patients with pneumonia, improving the curative effect after a 2-week treatment course, ameliorating expectoration and promoting the absorption of pneumonia lesions.